Effect of the number of fat layers on expansion of Danish pastry during proving and baking. (August 2015) - Deligny, C.; Lucas, T.
Highlights: Maximal lift was obtained for a lower number of fat layers (32) and was smaller (65%) than for puff pastry. The number and size of bubbles were highly dependent on the number of fat layers. Fat layers did not affect expansion during proving. The total height of paste after sheeting always exceeded the space between rollers, by 37% to 61%. Height of paste after sheeting did not change for a cumulative stress higher than 0.95. Abstract: The effects of the number of fat layers (4–162 layers) on expansion and loss of CO2 and water in Danish pastries (yeasted puff pastry) were studied at each processing step. Proving contributed to most of the expansion (200–300%) and no specific role of fat layers was evidenced at this stage; this was confirmed by measurements of CO2 released. Relative expansion during baking ranged from 20% to 65% for 4 to 32 fat layers and remained unchanged above 48 layers. Images cross sections of Danish pastry showed that bubbles were few for 4 fat layers, but very large (3–4 cm) and elongated in the direction of layering. For high numbers of fat layers, bubbles were numerous, smaller and round (2–7 mm). The loss of water vapor retention during baking in relation to fragmentation of fat layers during sheeting explained the leveling-off of expansion and the decreasing size of bubbles.